Breastfeeding initiation and duration: links to physical, mental and behavioural health in US children aged 3–5 years - Xin Wang; Lei Shi; Li Cai; Li-Zi Lin; Qiang Feng; Ning Pan; Kang-You Li; Sai-Jun Huang; Yingqian Chen; An-Qi Ren; Xu-Chu Weng (BMJ Nutrition, Prevention & Health)
Background Breastfeeding is a cornerstone of child health. We investigated the associations of any breastfeeding initiation and duration with physical, mental and behavioural health conditions among children aged 3–5 years in the USA.Methods Data were derived from the 2016 to 2022 National Survey of Children’s Health, which is a national, population-based, cross-sectional study. A total of 40 280 children aged 3–5 years were included. Any breastfeeding initiation and duration, physical (asthma, allergies, arthritis, cerebral palsy, diabetes, epilepsy or seizure disorder, heart conditions or severe headaches), mental (anxiety or depression) and behavioural (Tourette syndrome, attention-deficit/hyperactivity disorder or behavioural/conduct problems) health conditions were measured using parent-reported questionnaires.Results Any breastfeeding was significantly associated with lower odds of behavioural health conditions (OR=0.76, 95% CI: 0.58 to 0.99) and marginally with mental health conditions (OR=0.70, 95% CI: 0.48 to 1.02, p=0.067). There was a significant non-linear trend between any breastfeeding duration and having a mental or behavioural health condition (all Pnon-linear<0.001). The intervals of significant associations were 7.3–23.4 months for mental condition and 6.8–24.1 months for behavioural condition (the most associated points at 15.6 and 15.3 months). There were no significant associations of any breastfeeding initiation and duration with physical health.Conclusions Any breastfeeding was linked to better behavioural health and marginally to mental health, with no association found for physical health among children aged 3–5 years in the USA. Any breastfeeding duration of approximately 15 months appears to have the strongest association with promoting children’s mental and behavioural health.